Assessment of Pseudoephedrine Sulfate by Spectrofluorometric Method in Pharmaceutical Formulations By means of Derivatization 2-Chloro-7-Nitrobenzo ‐2‐Oxa‐1, 3‐Diazole - Mahdi, Noor Mahmood; Hadi, Araa Ali (Technium Sustainability, 2025)
To identify a sympathomimetic medication, pseudoephedrine hydrochloride, a novel, profoundly delicate, and explicit spectrofluorometric technique has been devised. The current technique produced a highly luminous product that was measured at 532 nm (excitation at 475 nm) by derivatization with 2-Chloro-7-Nitrobenzo ‐2‐Oxa‐1, 3‐Diazole in phosphate buffer at pH 7.8. The fluorescence intensity and pseudoephedrine hydrochloride concentration were shown to have a linear relationship and strong correlation at optimal conditions, ranging from 0.5 to 5 mg/mL-1. The suggested approach was effectively used to test for pseudoephedrine hydrochloride in commercial pharmaceutical formulations with high precision and accuracy, free from common additive interference. A statistical analysis of the data using a recognized methodology revealed good agreement and demonstrated that the accuracy and precision did not differ significantly. The reaction’s stoichiometry was established, and the reaction route was hypothesized.